1979
DOI: 10.1007/bf00423150
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of cyclic AMP and glucose in isolated islets from Acomys cahirinus

Abstract: Summary. Glucose-induced cyclic (3H) AMP accumulation, insulin secretory responses and the metabolism of glucose were studied in pancreatic islets from Acomys cahirinus. 27.7 mmol/1 of glucose stimulated neither islet cyclic (3H) AMP accumulation nor insulin release during the first 5 min of incubation. Stimulation by glucose of cyclic (3H) AMP was observed after 15 min of incubation and insulin release was markedly stimulated between 15 and 30 min. The utilization of glucose, measured as the production of (3H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Work from this laboratory [23] and elsewhere [4,[24][25][26] presented evidence to suggest that the stimulation of B cell cyclic AMP levels by glucose is particularly important for the expression of normal first phase insulin release. By the present direct measurements of islet cyclic AMP we were able to confirm earlier observations using prelabelling of islets with 3H-adenine [20], that the adenylate cyclase system of the spiny mouse is essentially glucoseinsensitive, in keeping with the blunted first phase insulin response to the sugar. Although cyclic AMP levels could be raised by the phosphodiesterase inhibitor IBMX and the adenylate cyclase stimulator forskolin in Acomys islets to the same extent as in rat islets, complete insensitivity of the enzyme to glucose was retained in either case.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Work from this laboratory [23] and elsewhere [4,[24][25][26] presented evidence to suggest that the stimulation of B cell cyclic AMP levels by glucose is particularly important for the expression of normal first phase insulin release. By the present direct measurements of islet cyclic AMP we were able to confirm earlier observations using prelabelling of islets with 3H-adenine [20], that the adenylate cyclase system of the spiny mouse is essentially glucoseinsensitive, in keeping with the blunted first phase insulin response to the sugar. Although cyclic AMP levels could be raised by the phosphodiesterase inhibitor IBMX and the adenylate cyclase stimulator forskolin in Acomys islets to the same extent as in rat islets, complete insensitivity of the enzyme to glucose was retained in either case.…”
Section: Discussionsupporting
confidence: 86%
“…More important, the dynamics of insulin release are strikingly reminiscent of those seen in glucose intolerant man [15,17,20], in that first phase response to glucose is grossly reduced, while second phase response is less impaired [17]. We have previously shown that if Acomys islets are primed with glucose to generate time-dependent potentiation, the kinetics of the insulin response to a subsequent glucose stimulus are markedly improved, a near-normal first phase release being elicited [17].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The mice showed a low response to various secretagogues in the initial and late phases of insulin release, including glucose, arginine, glucagon, and cyclic AMP both in vivo and in vitro Junod et al 1969;Rabinovitch et al 1975). This response was attributed to several factors such as low islet adenylate cyclase activity, low cAMP response of ␤-cells after a glucose load, low amount of vincristine precipitable material in ␤-cell microtubuli through which insulin granules are extruded, and scarcity of autonomic islet innervation (Grill and Cerasi 1979;Gutzeit et al 1974;Malaisse-Lagae et al 1975;Orci et al 1970). These findings were first interpreted as resulting from a genetic mutation in the animals maintained in captivity, but it is more likely that such responses of the islets may be a native characteristic of animals living in a desert environment, aimed at the protection of the pancreas against overstimulation.…”
Section: Characteristics Of Spiny Mice In the Geneva Colonymentioning
confidence: 89%
“…To elucidate the metabolic defect(s) of the/3 cells, suitable animal models for Type 2 diabetes are needed. The spiny mouse (Acomys cahirinus) is a semi-desert rodent which has been studied extensively as a model for Type 2 diabetes in man [8][9][10][11][12][13][14][15][16]. Bred in captivity, these animals demonstrate various degrees of glucose intolerance, become obese with age and develop hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%